Makna Nama Antipas, Bileam, dan Izebel serta Implikasinya terhadap Pembentukan Karakter - Aska Pattinaja; Andris Kiamani; Jani (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
One of the distinctive features of the book of Revelation is its abundant use of symbols, including names that serve as lessons and warnings to believers. Revelation 2:13, 14, and 20 mention three names—Antipas, Balaam, and Jezebel—that carry rich symbolic meaning. However, many scholarly studies on Revelation often overlook the theological significance of these figures as important messages for the church. Therefore, this research seeks to explore the meaning and relevance of these three names for character formation. Using a qualitative hermeneutic method focused on symbolic analysis, this study finds that Antipas represents faithfulness and integrity amid persecution; Balaam represents deceit and moral compromise, which calls for vigilance and ethical discernment; and Jezebel symbolizes immorality and idolatry, which must be rejected and guarded against. These messages provide crucial guidance for believers in building character and living righteously according to Biblical truth, especially in facing challenges in the last days.